Chiari type I malformation, syncope, headache, hypoglycemia and hepatic steatosis in an 8-year old girl: a causal association? - Alberto Spalice; Luigi Tarani; Francesca Del Balzo; Francesco Costantino; Enrico Properzi; Natascia Liberato (MDPI AG, 2010)
Chiari type I malformation (CMI) is a congenital hindbrain anomaly characterized by downward displacement of the cerebellar tonsils through the foramen magnum. Chiari type I malformation often presents with a complex clinical picture and can be sporadic or linked to a variety of genetic conditions. We report on a girl in whom Chiari type I malformation was associated with hypoglycemia, headache, vertigo, syncope and hepatic steatosis. We hypothesize that these symptoms are primarily a consequence of Chiari type I malformation.